2018
DOI: 10.26633/rpsp.2018.60
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of interventions to reduce motor vehicle crashes and their injuries among the general and working populations

Abstract: Objective To summarize the best available international scientific evidence on the effectiveness of interventions to reduce motor vehicle collisions and their consequences among the working and general populations. Methods A broad and systematic review was conducted of the literature available in biomedical databases and grey literature. At least two investigators working in parallel performed data extraction, synthesis, and risk of bias analysis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…Driving under the influence of alcohol is prohibited and legally sanctioned in most countries, as alcohol drastically impairs the required cognitive and motor skills, thus putting the driving individual as well as co-drivers and bystanders at substantial risk of accidents and injury [1][2][3][4][5]. Even after the acute intoxication has worn off and blood alcohol levels (BAC) have returned to 0.00% , cognitive, attentional, and psychomotor functions likely remain impaired to a certain degree [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Driving under the influence of alcohol is prohibited and legally sanctioned in most countries, as alcohol drastically impairs the required cognitive and motor skills, thus putting the driving individual as well as co-drivers and bystanders at substantial risk of accidents and injury [1][2][3][4][5]. Even after the acute intoxication has worn off and blood alcohol levels (BAC) have returned to 0.00% , cognitive, attentional, and psychomotor functions likely remain impaired to a certain degree [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Los datos de la Policía Nacional del Perú, del 2004Perú, del -2016, corroboran que los Choques de tránsito y los atropellos están correlacionados con el crecimiento del parque automotor hasta el 2014, y evidencian que estos en el Departamento de Lima, tienen un comportamiento diferente al comportamiento nacional y del resto del país, ya que Lima tiene una tendencia lineal, que no refleja los incrementos nacionales (Málaga et al, 2018), por lo que nuestros hallazgos de disminución de las muertes violentas y en especial de las victimas alcoholizadas, debería ser consecuencia de la restricción de horarios de expendio. Esta medida con otros programas que regulen enfatice y penalice a los conductores bajo la influencia del alcohol, mejoren la seguridad en el manejo, mejoren la infraestructura de carreteras y establezcan programas de educación y castigos a los conductores con antecedentes de violaciones de tránsito (Lefio et al, 2018), evidenciado en Brasil que reducen los eventos de tránsito (De Souza & Mathias, et al, 2018).…”
Section: Discussionunclassified
“…To date, several reviews have been carried out to identify, examine, and study the effectiveness of specific preventative approaches in particular regions or countries [7,23,[25][26][27][28][29][30][31][32][33][34][35][36]. A previous scoping review has reported on interventions to reduce road traffic injuries, but this was limited to the African continent, and another review has specifically focused on physiotherapy after neurotrauma [37,38].…”
Section: Introductionmentioning
confidence: 99%